2011
DOI: 10.1042/bj20101487
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between ubiquitin E2 enzymes and TRIM proteins

Abstract: The TRIM (tripartite motif) family of proteins is characterized by the presence of the tripartite motif module, composed of a RING domain, one or two B-box domains and a coiled-coil region. TRIM proteins are involved in many cellular processes and represent the largest subfamily of RING-containing putative ubiquitin E3 ligases. Whereas their role as E3 ubiquitin ligases has been presumed, and in several cases established, little is known about their specific interactions with the ubiquitin-conjugating E2 enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 48 publications
3
91
0
2
Order By: Relevance
“…This heterodimeric E2 has been reported to be one of the cognate E2s for TRIM25 and TRIM32, and thus, we used it to compare their ability to catalyse the formation of poly‐ubiquitin chains independent of the nature of the substrate (Zeng et al , 2010; Napolitano et al , 2011; Zhang et al , 2012). As observed in the discharge assays, the monomeric TRIM25 RING‐only and B‐box‐containing fragments are active (Figs 2E and F, and EV1), whereas TRIM32 only showed activity for dimeric constructs (Figs 2G and H, and EV1).…”
Section: Resultsmentioning
confidence: 99%
“…This heterodimeric E2 has been reported to be one of the cognate E2s for TRIM25 and TRIM32, and thus, we used it to compare their ability to catalyse the formation of poly‐ubiquitin chains independent of the nature of the substrate (Zeng et al , 2010; Napolitano et al , 2011; Zhang et al , 2012). As observed in the discharge assays, the monomeric TRIM25 RING‐only and B‐box‐containing fragments are active (Figs 2E and F, and EV1), whereas TRIM32 only showed activity for dimeric constructs (Figs 2G and H, and EV1).…”
Section: Resultsmentioning
confidence: 99%
“…TRIM family members are a class of novel ring-finger E3 ligases that have been shown to ubiquitinate a number of different proteins (30)(31)(32). To assess whether TRIM27 ubiquitinates PI3KC2β, PI3KC2β was expressed with His-tagged ubiquitin either alone or together with TRIM27 and ubiquitinated PI3KC2β was assessed following purification with Nickel (Ni)-NTA beads.…”
Section: Trim27mentioning
confidence: 99%
“…TRIM family proteins are characterized by the presence of the tripartite motif, which consists of a ring finger, Zn 2+ binding motifs referred to as "B boxes," and a coil-coil domain (29,30). TRIM family members have been shown to regulate a plethora of cellular pathways, including apoptosis, the cell cycle, and antiviral activity, and recent evidence has indicated that this family of proteins regulates some of these processes by functioning as a novel class of Really Interesting New Gene (RING) E3 ubiquitin ligases (29)(30)(31). We now show that by ubiquitinating PI3KC2β, TRIM27 inhibits PI3KC2β's kinase activity, resulting in decreased KCa3.1 channel activity and decreased TCR-stimulated Ca 2+ influx and cytokine production, thereby identifying TRIM27 as a unqiue negative regulator of CD4 T cells.…”
mentioning
confidence: 99%
“…TRIM family members have been implicated in a wide variety of biological processes, including transcriptional regulation, apoptosis, cell cycle regulation, cancer, and viral infection (22)(23)(24)(25)(26), and are characterized by a tandem array of three recognizable domains in their amino-terminal regions (27). The RING finger is a zinc-binding domain generally found within 20 residues of the amino terminus of TRIM family members and is thought to be responsible for TRIM protein interaction with E2 ubiquitin-conjugating enzymes (28,29). This is followed by the B-box, a zinc-binding domain of undefined function (30).…”
mentioning
confidence: 99%